PENGELOLAAN SAMPAH ORGANIK BERBASIS SKALA RUMAH TANGGA DI DESA LEBIH GIANYAR BALI - Indrawan, G.S.; Putra, I.N.G.; Brasika, I.B.M.; Karang, I.W.G.A.; Puspitha, N.L.P.R.; ., Widiastuti (Buletin Udayana Mengabdi; Vol 21 No 3 (2022): Buletin Udayana Mengabdi, 2022)
Composting technology and eco-enzyme are two alternatives that can be done to reduce organic waste pollution in the environment. The purpose of this activity is to provide information to the community at the household scale regarding the application of composting technology and eco-enzyme in organic waste management, so that it is expected to be an entrepreneurial idea and an effort to save the environment. The service was carried out in the village of Lebih, Gianyar, Bali. The activity was carried out through the stages of site survey, socialization, training on composting and eco-enzyme using organic waste. The output of this activity is expected to be fostered by households in the Lebih Coastal Area, to be able to develop technology and ideas the entrepreneurial spirit of environmentally-based communities, and to increase public awareness in efforts to save the environment in general. The implementation of the service on composting and eco-enzyme training was attended by the community of Lebih Village, which consisted of village officials, village residents, village youths, and academics from Udayana University. The training was provided by two speakers from Urban Kompos and Griya Luhu. In the implementation of the training, the community was very enthusiastic and able to understand the training materials. It is hoped that the community will continue to manage waste properly, and in the future, it can be and sustainable, so that the problem of waste, especially on a home scale, can be resolved.   Keywords : Eco-enzyme, composting, lebih beach, environmentally friendly